Reproductive Performance and Repeatability Estimation of Some Traits of Crossbred Cows in Savar Dairy Farm - Islam, MS; Akhtar, A; Hossain, MA; Rahman, MF; Hossain, SS (Journal of Environmental Science and Natural Resources, 2018)
The study was conducted on 244 crossbred cows of CCBS Savar, Dhaka to evaluate the effect of different genetic groups on their lifetime performance of various reproductive traits using twenty years data. Data were accumulated from a prescribed data sheet maintained by Central Cattle Breeding Station, Dhaka. Genetic groups for this experiment were (LF), (LJ), (LH x F), (LF x LF) and (LJ x LJ). The studied parameters were age at puberty, service per conception, post-partum heat period, calving interval, total number of calving in lifetime. ANOVA showed that genetic groups had a significant effect on age at puberty, post-partum heat period, total number of calving in lifetime and calving interval (P<0.05). From result it was found that earliest age at puberty were in L x F (749.27±99.01), service per conception, postpartum heat period was lower in L x F (1.60±0.19 and (145.75±94.44 days respectively). Calving interval was lower in L x J (411.18±136.87 days) and almost similar results were obtained for L x F (432.26±96.26 days). Total number of calving in lifetime were observed higher in (LH x F) with mean of 1468.30±198.58 days. J. Environ. Sci. & Natural Resources, 10(2): 87-94 2017